Manifesta 7 : Scenarios. - Manifesta Trentino South Tyrol 2008; Amin, Shahid; Budak, Adam; Cavarero, Adriana; Dolar, Mladen; Franke, Anselm; Green, Renée; Meinecke, Thomas; Neath, Glen; Obexer, Margareth; Peleg, Hila; Raqs Media Collective; et al. (Milano : Silvana Editoriale, 2008)
Hampton, Ant ; Hoezl, Hannes ; Gamper, Martino ; Brave New Alps ; Kahlen, Timo ; Rahm, Philippe ; Farocki, Harun ; Goldt, Karo ; Gottheim, Larry ; Kels, Karel ; Snow, Michael ; et al.
European Biennial of Contemporary Art, Trentino South Tyrol, 19 July - 2 November 2008
This publication assembles the complete versions of the texts spoken by the fortress to the visitors.
kunstcatalogus